Specifics of a foreign language training organization of students of technical specialties based on dialogic teaching - Лапіна, Вікторія Олексіївна (Pedagogy of Higher and Secondary Education, 2016)
Lapina V. О. Specifics of a foreign language training organization of students of technical specialties based on dialogic teaching. The peculiarities of a dialogic teaching organization of foreign languages based on cooperative pedagogy in the context of a foreign language training of students of technical higher educational institutions have been considered in the article. They contribute to maximum realization of didactic potential of educational dialogue as an effective means of forming and developing some skills. The key features of teaching foreign languages by using dialogic means of learning in technical higher educational institutions (communicative oriented approach; problematic content/context of didactic material; case-study learning activity; active methods and forms of teaching) have been highlighted. The scientific works on communicative aspect of learning have been analyzed, that allowed to examine this issue in the context of a dialogic teaching of foreign languages and to highlight communication as its key feature. The various aspects of a problem-based teaching of foreign languages organized and based on the pedagogy of cooperation have been studied. Such learning process is characterized by a high level of problems and is implemented by a system of problem-solving tasks. Students acquire new knowledge, develop intellectual, speech and communication skills and creativity through/by activation of thinking while self-defining and solving problems. A case-study approach has been highlighted as one of the key feature of a dialogic teaching of foreign languages, which is an effective means of speech activity stimulation. It contributes to students’ awareness of real social and professional situations for realizing foreign language communication. The interactivity of teaching foreign languages by means of educational dialogue has been considered. The priority of active methods of learning activity (business/role-plays, case-study discussions, problem solving tasks etc.), which provide an effective interaction of students in class, has been justified.